FRUIT CHARACTER PERFORMANCE OF 26 GENOTYPES OF MELON (Cucumis melo L.) IN WICK HYDROPONIC CULTIVATION SYSTEMS - Helfi Eka Saputra; Umi Salamah; Welly Herman; Marlina Mustafa (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2021)
[FRUIT PERFORMANCE OF 26 GENOTYPES OF MELON (Cucumis melo L.) IN WICK HYDROPONIC CULTIVATION SYSTEMS]. Fruit performance is determining quality factor for melon fruit. This research aimed to obtain the melon genotype which has the best fruit quality by the cultivation of the wick hydroponic system. The research was conducted from June to September 2020 in the greenhouse of the Agronomy Laboratory, Bengkulu University. The study was compiled with a single-factor of the melon genotypes using randomized complete block design (RCBD) with two replications. The genotypes were G23, G27, G28, G29, G38, G39, G40, G41, G42, G43, G45, G46, G47, G48, G49, G52, G53, G55, G57, G58, G60, G62, G63, G64, G65, and G66. The best genotypes for fruit length characters were G28 and G42. The best genotypes for fruit diameter character were G52, G58, G60, G64, and G66. The best genotype for fruit thickness character was G43. The best genotype for total dissolved solids character was G45. The best genotypes for fruit weight characters were G58, G66, and G60.